Base Case Analysis of a HYSOL Power Plant. (May 2015) - Servert, J.F.; Cerrajero, E.; López, D.; Yagüe, S.; Gutierrez, F.; Lasheras, M.; Miguel, G. San
Abstract: Concentrating solar power (CSP) plants are regarded as an alternative solution for electricity generation. The main drawback of this technology is related to the intermittent and seasonal nature of the solar irradiation. As a consequence, most CSP plants have a reduced capacity factor and difficulties to supply electricity on demand to the grid. The integration of energy back-up systems may contribute to increasing power generation capacity and stability. Several options are being developed at present which are based on the incorporation of Thermal Energy Storage (TES) and also the use of auxiliary fuels. HYSOL is a new concept in CSP technology that relies on the integration of a molten salt TES system operating in hybrid mode with a biogas turbine with a Heat Recovery System (HRS). This paper illustrates the methodology and first results obtained during the development of the static model, considering a Base Case of HYSOL configuration. The study of this Base Case allows evaluating the impact of HYSOL technology, providing preliminary plant information and defining the required tools to be used in the project.